The Impact Of Discipleship And Empowerment Of The Laity To The Growth Of Church Betesda Indonesia Gateway, Sidoarjo - Purnomo Adi (Theological Journal Kerugma, 2021)
This article is entitled “The Impact of Discipleship and empowerment of the Laity to the Growth of Gereje Betesda Indonesia Gateway in Sidoarja. In this matter, there is questioned whether the discipleship and empowerment of the laity can improve the growth of a church specifically in Gereja Betesda Indonesia Gateway in Sidoarjo. This impact is measured with the use of coefficient correlation of Pearson and analysis of double regression, the test of T, and variants analysis. Descriptive analysis is conducted to analyze the growth of Gereja Betesda Indonesia Gateway in Sidoarjo, according to the demographical group.Then, it is found out that the discipleship and empowerment of the laity, gain impact which shows 59,4% to the growth of Gereja Betesda Indonesia Gateway in Sidoarjo All of the variables have a correlation partially to the significant growth of the church .